2019
DOI: 10.1111/pim.12623
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in monocyte subsets and cytokine production after TLR activation in American Cutaneous Leishmaniasis

Abstract: Phenotypic and functional aspects of monocytes from Localized Cutaneous Leishmaniasis (LCL) patients were evaluated. The frequencies of monocyte subsets and TLR2/TLR4 expression were evaluated in fresh peripheral blood whereas cytokine production was evaluated in whole blood cell cultures stimulated with TLR agonists or Leishmania braziliensis antigen (Ag). CD16+ monocytes frequency was increased in patients compared with controls. A TLR4 agonist (LPS) induced expression of TNF and IL‐10 in monocyte subsets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…It follows that the identification of mechanisms capable of modulating this response may aid in the development of immunomodulatory therapies. The premise of our study was based on previous reports demonstrating that monocytes from CL patients express more TLR2 and TLR4 in association with elevated TNF production (16,32). The present results indicate that the neutralization of these receptors can indeed modulate the exacerbated inflammatory response documented in CL caused by L. braziliensis.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…It follows that the identification of mechanisms capable of modulating this response may aid in the development of immunomodulatory therapies. The premise of our study was based on previous reports demonstrating that monocytes from CL patients express more TLR2 and TLR4 in association with elevated TNF production (16,32). The present results indicate that the neutralization of these receptors can indeed modulate the exacerbated inflammatory response documented in CL caused by L. braziliensis.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the neutralization of TLR2 and TLR4 decreased TNF expression in monocytes after stimulation with SLA. These results seem to indicate that, in our in vivo experimental model, even after inducing infection and the partial clearance of parasites, the presence of SLA is able to continue stimulating the immune response by increasing the expression TLR2 and TLR4, in addition to the production of inflammatory molecules (32).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The contribution of TLR4 during Leishmania infection and treatment has been extensively studied, since it is considered to be important for efficient parasite control during innate immune responses [29,[52][53][54][55][56]. A previous study performed on whole blood of dogs stimulated with L. infantum antigen and different TLRa, demonstrated that TLR4a induced a potent pro-inflammatory cytokine stimulation [53].…”
Section: Discussionmentioning
confidence: 99%
“…In homeostasis, in adult life, evidence shows that classical monocytes migrate into tissues, giving rise to resident macrophages with diverse functions according to tissues where they reside or remain as monocytes, which act as a peripheral reservoir of these cells, and non‐classical monocytes are considered patrolling cells searching for particles or endothelium injury in blood vessels (Canè et al., 2019; Guilliams et al., 2018; Patel et al., 2017). In inflammatory conditions, classical monocytes are considered inflammatory cells and migrate into injured tissues with high functional plasticity; however, among monocyte subsets, those expressing CD16 have been mostly detected in several inflammatory/infectious diseases, functioning as antigen‐presenting cells and potent producers of cytokines depending on the stimuli (Boyette et al., 2017; Cros et al., 2010; Guilliams et al., 2018; Quixabeira et al., 2019; Ziegler‐Heitbrock, 2007). The evaluation of monocytes in PD has demonstrated that these cells are hyperresponsive to inflammatory stimuli (Grozdanov et al., 2014).…”
Section: Introductionmentioning
confidence: 99%